2018
DOI: 10.1002/chem.201801273
|View full text |Cite
|
Sign up to set email alerts
|

5‐Aza‐7‐deaza‐2′‐deoxyguanosine and 2′‐Deoxycytidine Form Programmable Silver‐Mediated Base Pairs with Metal Ions in the Core of the DNA Double Helix

Abstract: 5-Aza-7-deaza-2'-deoxyguanosine (dZ) forms a silver-mediated base pair with dC. The metal ion pair represents a mimic of the H-bonded Watson-Crick dG-dC pair. The modified nucleoside displays a similar shape as the parent 2'-deoxyguanosine from which it can be constructed by transposition of nitrogen-7 to the bridgehead position-5. It lacks the major groove binding site as the positional change moves the dG- acceptor position from nitrogen-7 to nitrogen-1. As a shape mimic of dG, it fits nicely in the DNA doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
15

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 67 publications
1
15
0
15
Order By: Relevance
“…The study indicated that the Δ T m values of duplexes containing a C‐C, a C‐A or a C‐T mismatch on addition of Ag I ions are +12, +9, and +3 to +6 °C, respectively. This order of stabilization is fairly consistent with our results, although this is not always the case . The stability changes should depend to some degree on the neighboring sequences…”
Section: Resultssupporting
confidence: 92%
“…The study indicated that the Δ T m values of duplexes containing a C‐C, a C‐A or a C‐T mismatch on addition of Ag I ions are +12, +9, and +3 to +6 °C, respectively. This order of stabilization is fairly consistent with our results, although this is not always the case . The stability changes should depend to some degree on the neighboring sequences…”
Section: Resultssupporting
confidence: 92%
“…By replacing the bridgehead C5 atom of 7C Gbyanitrogen atom, 5-aza-7-deazaguanine 5N7C Gi sf ormed. 5N7C Gh as ap rotonation pattern different from that of the parent nucleobase guanine.I np articular,t he endocyclicN 1a tom [18] d) 5N7C G-Ag I -C. [19] R, R' = DNA backbone.…”
Section: Ag I -Mediated Base Pairs Involving Purine Derivativesmentioning
confidence: 99%
“…Figure 2d shows the resulting 5N7C G-Ag I -C base pair. [19] Compared to 7C G, 5N7C Gisbetter suited for ap rogrammed Ag I -modification of the G:Cb ase pair, because the 5N7C G:Cp air represents am ispair in the absence of Ag I ,but astrongly stabilizing metal-mediated base pair in its presence.S imilar to 7C G, weak binding of one additional Ag I ion per base pair has been observed for 5N7C G, too.…”
Section: Ag I -Mediated Base Pairs Involving Purine Derivativesmentioning
confidence: 99%
“…Such mismatches are formed by homo base pairs of dT-dT,d C-dC, or dG-dG, as well as by the hetero pair of 5aza-7-deaza-2'-deoxyguanosine with 2'-deoxycytidine. [20] A recent X-ray structure determination of ad odecamer duplex that could be expectedt of orm silver-mediated dA-dT and dG-dC base pairs showed insteadt hat silver-mediated homo pairs of dT-dT,d G-dG, and dC-dC were formed, andt hat the dA residues werel ooped out. [6a] Due to the different stabilities of bidentated A-dT and tridentate dG-dC pairs, one may be preferentially convertedi nto as ilver-mediated pair.N evertheless, as already discussed by Gwinn, [8g] silver-mediated homo pairs of dC-dC or dG-dG are more stable than silver-mediated dA-dT or dG-dC pairs.…”
Section: Performance Of Duplexes Upon Increasing the Amounto F Silvermentioning
confidence: 99%